Linguistic Risk-Taking: Exploring the Perspective of Future Language Educators (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2026)
This article relates Linguistic Risk-Taking (LRT) to the context of future language educators. LRT refers to language learners stepping beyond their comfort zones by using a target language in challenging linguistic and communicative situations–experiences that can lead to personal growth, enjoyment and a sense of accomplishment. While LRT has been recognized as a valuable element in language learning, its role among teacher trainees remains underexplored. Yet, this group is uniquely positioned to influence LRT in their future classrooms, acting as practitioners and role models for their future students. This is why raising awareness among teacher candidates about the educational and emotional benefits of LRT is important. Choosing a participatory approach, a survey of 81 university students training to become English teachers was conducted. The results reveal insights into their perceptions of LRT and their preferences for tailoring the Canadian LRT initiative (Slavkov & Séror, 2019) to their context.